Country report : Yugoslavia - Economist Intelligence Unit (Great Britain) (Economist Intelligence Unit, 1986)
"Analysis of economic and political trends". Continues in part: Quarterly economic review of Yugoslavia, ISSN 0142-3983.Continued by: Country report. Yugoslav republics.